Analysis of Loss of Skeletal Muscle Mass from bioimpedance findings in a cohort of patients undergoing Bariatric Surgery (Research, Society and Development, 2020)
Objectives: The present study aims to investigate the development of MME loss in individuals undergoing bariatric surgery using bioimpedance. Method: Retrospective and observational cohort study, data were only collected and analyzed after approval by the Research Ethics Committee. The patients included were followed up with clinical and bioimpedance assessments for at least 6 months. The variables of interest were: epidemiological, anthropometric, pre- and post-surgery data, and results of serial bioimpedances. The data are presented in relative and absolute frequency, the comparison of means was done by the Student's T test. The average survival time until the development of low MME was estimated by the Kaplan-Meier model. Α = 5% was defined. Results: 30 patients were included, 80% of whom were female. The sample had an average age of 39 years. An average difference of 27.4 kg in body mass was found, when compared to the last anthropometric assessment with the values ​​prior to surgery, which proved to be statistically significant (p